Silicon Solar Cells: Multifunctional Effect of p‐Doping, Antireflection, and Encapsulation by Polymeric Acid for High Efficiency and Stable Carbon Nanotube‐Based Silicon Solar Cells (Adv. Energy Mater. 1/2020). Issue 1 (7th January 2020) - Qian, Yang; Jeon, Il; Ho, Ya‐Lun; Lee, Changhyun; Jeong, Sujeong; Delacou, Clement; Seo, Seungju; Anisimov, Anton; Kaupinnen, Esko I.; Matsuo, Yutaka; Kang, Yoonmook; Lee, Hae‐Seok; et al.
Abstract : In article number 1902389, Il Jeon, Shigeo Maruyama, and co‐workers demonstrate the multifunctional effects of Nafion polymer on carbon nanotube‐based silicon solar cells. Nafion induces effective and permanent p‐doping in carbon nanotubes. At the same time, it functions as an effective anti‐reflective layer thanks to its low refractive index. Finally, its chemical and physical robustness enables strong encapsulation of the device.